11C-Choline PET/CT for Restaging of Bladder Cancer. (January 2015) - Graziani, Tiziano; Ceci, Francesco; Lopes, Flavia Lobo; Chichero, Josè; Castellucci, Paolo; Schiavina, Riccardo; Bianchi, Lorenzo; Chondrogiannis, Sotirios; Colletti, Patrick M.; Costa, Stefano; Rubello, Domenico; Fanti, Stefano
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to evaluate of 11C-choline PET/CT in bladder cancer (BC) patients with suspected relapse after primary therapy. Methods Twenty-five BC patients with surgery (21 [84%]) or radiotherapy (4 [16%]) with curative intent had PET/CT for suspicion of relapse. Mean TNM was T2b N0 M0 (range, T1a N0 M0 to T4 N2 M0), whereas mean age was 71.3 years (range, 50-85 years). Nine (36%) of 25 were treated with adjuvant or salvage chemotherapy within 6 months before PET/CT. Positive findings were validated by histology or correlative imaging and/or clinical follow-up lasting at least 12 months. Age, TNM, histology, previous chemotherapy, and type of primary treatment were correlated with PET/CT positivity by univariate and multivariate binary logistic regression analysis. Results 11C-choline PET/CT was positive in 16 (64%) of 25. Six (37.5%) of 16 were positive in residual bladder/bladder bed, with 2 local false positive (FP) and 1 false negative (FN) on lymph nodes (LNs); 3 of 16 patients had PET-positive LNs with 1 FP; 1 of 16 patients showed distant metastases. Two (12.5%) of 16 had positive residual bladder/bladder bed and locoregional LNs; 1 (6.3%) of 16, residual bladder/bladder bed and bone; metastasis, 1 (6.3%) of 16 residual bladder/bladder bed and lung metastasis; 2 (12.5%) of 16, LN and distant metastasis. Five (56%) of 9 of PET negatives were FN in residual bladder/bladder bed. Eighteen (72%) of 25 were validated by histology, with 7 (18%) of 25 by correlative imaging and/or clinical follow-up. 11C-choline PET/CT was sensitive, specific, and accurate, with good positive and negative predictive values for local relapse of 66.7%, 84.6%, 76%, 80%, and 73.3% and 90%, 93.3%, 92%, 90%, and 93.3% for LNs and distant relapse, respectively. No FP or FN was detected for distant metastasis. None of the investigated factors were statistically significant. Conclusion 11C-choline PET/CT is useful for restaging BC suspected of relapse, especially for the evaluation of LN or distant metastases.